Teaching Design and Implementation Strategies for Short-Form Tai Chi (Eight Methods and Five Steps) in Junior High School Physical Education in the Era of AI and National Fitness - Feng, Xiaoou (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details